2017
DOI: 10.5897/ajar2016.11370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant density on oil yield of safflower

Abstract: The definition of the ideal plant population is important for good safflower agricultural management in Brazil, as they are gaining importance as oleaginous plant. Two experiments were conducted in an Rhodic Acrudox in 2014 in Cascavel, PR, Brazil, to evaluate the effect of plant density on growth, yield components and grain yield in safflower oil during autumn and winter seasons. The experimental design was a randomized complete block design with three replications and four plant densities per meter (5, 10, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The plants grown with 30 cm and 45 cm row spacing gave higher average plant heights than plants grown with 15 cm row spacing (Table 2). In studies on the effect of planting density on plant height in safflower, it was generally seen that plant height increased in crowded densities compared to uncrowded densities (Omidi and Sharifmogadasi, 2010;Zarei et al, 2011;Hamza, 2015;Köse and Bilir, 2017;Sampaio et al, 2017;Çalışkan and Yüksel, 2022), while in some studies, similar to our findings, it has been reported that plant height decreases with an increase in plant density (Yau, 2009;Noroozi and Kazemini, 2013). The relationship between plant density and plant height is related to the competition between plants in terms of light, air, water and nutrients.…”
Section: Resultssupporting
confidence: 88%
“…The plants grown with 30 cm and 45 cm row spacing gave higher average plant heights than plants grown with 15 cm row spacing (Table 2). In studies on the effect of planting density on plant height in safflower, it was generally seen that plant height increased in crowded densities compared to uncrowded densities (Omidi and Sharifmogadasi, 2010;Zarei et al, 2011;Hamza, 2015;Köse and Bilir, 2017;Sampaio et al, 2017;Çalışkan and Yüksel, 2022), while in some studies, similar to our findings, it has been reported that plant height decreases with an increase in plant density (Yau, 2009;Noroozi and Kazemini, 2013). The relationship between plant density and plant height is related to the competition between plants in terms of light, air, water and nutrients.…”
Section: Resultssupporting
confidence: 88%
“…According to the analysis of variance table, irrigation and fertilizer had significant effect at 1% probability level for seed oil yield (Table 9). Considering that oil yield is calculated by multiplying the oil percentage by grain yield (Sampaio et al, 2017) and because in this experiment the highest oil percentage and highest grain yield were obtained from irrigation treatment with municipal wastewater and combined fertilizer and chemical fertilizer use, therefore, the highest oil yield was obtained from the same treatment (Table 7).…”
Section: Oil Percentage and Seed Oil Yieldmentioning
confidence: 98%
“…According to MAPA (Ministry of Agriculture, Livestock and Supply), in the year of 2012, the country imported the value of US$ 6.1 millions of "sunflower or safflower oils" (Brazil, 2013a), nevertheless, without percentage distinction among the species. In the 1990s, the safflower was introduced in the South region of the country as ornamental plant, in virtue of climate conditions, however, the great incidence of pathogens in all the productive cycle, had its cultivation reduced gradually (Santos and Silva, 2015;Sampaio et al, 2017). However, this species presents itself as an alternative of cultivation in the country, requiring economic-scientific investment for the increase of seed productivity, with phytosanitary quality.…”
Section: Introductionmentioning
confidence: 99%